The Impact of Health Education on The Level of Knowledge About Hypertension and Posbindu - Iftita, Magumi Avrora; Muthoharoh, Nor Amalia (Health & Medical Sciences, 2024)
The aim of this research is to determine whether or not there is an impact of health education on increasing public knowledge about hypertension and posbindu in Tambakharjo Village, West Semarang District, Semarang City. The research results showed that there was a change in respondents' knowledge for good knowledge levels from an average of 66.66 (pretest) to 85.33 (posttest). Based on the t test, the sig value is obtained. 2 tailed is 0.000 (< 0.05). This means that health education actions have an effect on increasing respondents' knowledge about hypertension and posbindu. The conclusion of this research is that health education activities about hypertension and posbindu have a significant impact on increasing public knowledge in Tambakharjo Village, Semarang City.